Healthcare service quality model: A multi-level approach with empirical evidence from a developing country. Issue 8 (14th November 2016) - Sumaedi, Sik; Yarmen, Medi; Yuda Bakti, I. Gede Mahatma
Abstract : Purpose: The purpose of this paper is to develop and test a multi-level healthcare service quality (HSQ) model in Jakarta, Indonesia. Design/methodology/approach: The research used a quantitative research method. Data were collected via a survey with questionnaire. The respondents are 154 patients of a healthcare institution in Jakarta, Indonesia. Findings: The research result shows a multi-level HSQ model. The HSQ model consists of three primary dimensions, namely, healthcare service outcome, healthcare service interaction, and healthcare service environment. Healthcare service outcome has three subdimensions, i.e. waiting time, medicine, and effectiveness. Healthcare service interaction has three dimensions, namely, soft interaction, medical personnel expertise, and hard interaction. Healthcare service environment has two dimensions, which are equipment condition and ambient condition. Research limitations/implications: This research was only conducted in one healthcare institution in Jakarta, Indonesia. The data collection using convenience sampling method as well as the use of small sample size caused the limitation of the research results in representing across the customer of the healthcare institution. This study can be replicated with larger sample size and involving more healthcare institutions in order to examine the stability of the HSQ model. Practical implications: Healthcare institution's managers can use the HSQ model to monitor, measure, and improve their service quality. Originality/value: There is a lack of research that develops and tests HSQ model based on multi-level approach in the context of developing country. This paper has fulfilled the gap.